Estudo da perda de heterozigosidade de genes supressores de tumor em tumores odontogênicos mistos - Clarice Ferreira Galvão (2012)
Odontogenic tumors represent a group of lesions with clinical and pathological variables, derived from tissues that form the teeth. The evaluation of the loss of heterozygosity (LOH Loss of heterozygosity-) allows identifying changes in tumors and precancerous lesions. Although loss of heterozygosity (LOH) in regions of tumor suppressor is important for understanding the process of formation of neoplasms, few studies have been performed with this approach in the odontogenic tumors. In this study, LOH in a panel of nine markers for tumor suppressor regions on chromosomes 3p, 9p, 11p, 11q and 17p were analyzed in five samples of ameloblastic fibroma, three samples of ameloblastic fibro-odontoma and three samples of ameloblastic fibrosarcoma. The most frequently lost genetic loci were p53 (17p13, 62%) and CHRNB1 (17p13, 55%). LOH at the chromosome regions 3p24.3, 9p21 and 9p22 was identified only in ameloblastic fibrosarcoma. No sample showed LOH at the chromosomal loci 3p21.2 and 11q13.4. For the region 9p22-p13, LOH occurred in one sample of ameloblastic fibro-odontoma. The fractional allelic loss was calculated for each sample. The mean fractional allelic loss of the benign lesions (i.e., ameloblastic fibroma and ameloblastic fibro-odontoma) was 22%, whereas the mean fractional allelic loss of the malignant lesions (i.e., ameloblastic fibrosarcoma) was 74.6%. In conclusion, our results show a higher fractional allelic loss of ameloblastic fibrosarcoma compared to its benign counterparts. These data suggest that LOH may be useful in the diagnosis and understanding of the pathogenesis of mixed odontogenic tumors.